2017
DOI: 10.1021/acs.est.7b02037
|View full text |Cite
|
Sign up to set email alerts
|

Larval Red Drum (Sciaenops ocellatus) Sublethal Exposure to Weathered Deepwater Horizon Crude Oil: Developmental and Transcriptomic Consequences

Abstract: The Deepwater Horizon (DWH) incident resulted in extensive oiling of the pelagic zone and shoreline habitats of many commercially important fish species. Exposure to the water-accommodated fraction (WAF) of oil from the spill causes developmental toxicity through cardiac defects in pelagic fish species. However, few studies have evaluated the effects of the oil on near-shore estuarine fish species such as red drum (Sciaenops ocellatus). Following exposure to a certified weathered slick oil (4.74 μg/L ∑PAH) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 62 publications
7
82
2
1
Order By: Relevance
“…Although similar photo‐enhanced toxicities were observed with our tests, a direct comparison cannot be made with the above‐mentioned studies because different UV photoperiods, total exposure times, and total UV dose were applied. However, it can be concluded and confirmed that red drum are among the most sensitive fishes to crude oil and photo‐enhanced crude oil toxicity tested to date (Alloy et al 2017; Xu et al 2017).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Although similar photo‐enhanced toxicities were observed with our tests, a direct comparison cannot be made with the above‐mentioned studies because different UV photoperiods, total exposure times, and total UV dose were applied. However, it can be concluded and confirmed that red drum are among the most sensitive fishes to crude oil and photo‐enhanced crude oil toxicity tested to date (Alloy et al 2017; Xu et al 2017).…”
Section: Resultsmentioning
confidence: 73%
“…Specifically, water samples analyzed from Barataria Bay, Louisiana (USA), where red drum are known to spawn, revealed ∑PAH concentrations >200 μg/L at the beginning of May, which decreased over time to as high as 22 μg/L by the end of June (Whitehead et al 2012). Although only mortality was assessed as a measure for acute toxicity in the present study, it should be noted that crude oil induces other sublethal effects (e.g., cardiac and ocular function and development) to developing red drum at much lower concentrations (Khursigara et al 2017; Xu et al 2017; Magnuson et al 2018). Most likely these negative effects have later repercussions to the developing fish and subsequently jeopardize their survival in the natural environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, sub-lethal oil exposure in later life stage fish has important ecological implications, which is further compounded by the fact that the impairments following acute exposure (24-48 h) can be observed at least 6 weeks later Mauduit et al, 2019), and in some cases on much longer time scales (Zhang et al, 2017). In addition to the typical cardiotoxic impairments, work on the DWH oil spill has highlighted a suite of emerging toxicity endpoints in fish, including: impaired eye development (Xu et al, 2017) with subsequent reductions in visual acuity (Magnuson et al, 2018); reduced brain size (Xu et al, 2017), evidence for impaired neural function (Xu et al, 2017and altered behavior (Johansen et al, 2017Rowsey et al, 2019); evidence for mitochondrial dysfunction (Johansen and Esbaugh, 2019;Kirby et al, 2019;Xu et al, 2017Xu et al, , 2019; altered control of embryonic buoyancy (Pasparakis et al, 2017); impaired cholesterol biosynthesis (McGruer et al, 2019); impaired immune function (Bayha et al, 2017;Jones et al, 2017;Rodgers et al, 2018); and impaired hypothalamus-pituitaryinterrenal axis function (Reddam et al, 2017).…”
Section: Direct Effects Of Oil Exposurementioning
confidence: 99%
“…As a means to link bioavailability measurements for EDCs and fish response, a genomics approach offers a robust toolkit to associate the presence of these chemicals with genomic biomarkers. Advances in molecular methods, such as microarrays, quantitative PCR (q-PCR) and high-throughput sequencing (HTS) have substantially improved the sensitivity of analyses for assessing the biological effects of EDCs on animal physiology [ 23 , 25 , 26 , 27 , 28 , 29 , 30 ]. Recently developed genomics technologies have also facilitated assessment of the effects of xenobiotics in the environment on human health [ 31 ].…”
Section: Introductionmentioning
confidence: 99%